(untitled) (Gestão & Regionalidade, 2025)
This study aims to identify the Critical Success Factors in the use of renewable energy in foreign companies and discuss the contribution of these factors to the current Brazilian scenario. The research method is of an applied, qualitative and exploratory nature. Data collection was based on documentary and bibliographic research. We sought to verify in the international literature which factors contribute to companies from other countries making use of energy from renewable sources in their companies. We conclude that in several countries there are government incentives for the generation and use of energy from renewable sources by companies. The use of renewable energy is already part of the business strategy, with economic and environmental return, besides generating a positive image in the market. Many companies already use advanced technologies to develop a variety of renewable energy sources.